Katekese Tentang “Bangga Menjadi Orang Katolik” bagi Komunitas Mahasiswa Katolik Pu‘urere - Aurelius Fredimento; Gregorius Sebo Bito; Nong Hoban; Berty Sadipun; John M. Balan; Maximus Dhay Woa; Imelda Oko; Felix Welu (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2021)
The pride of being a true Catholic has gone down and also has been the symptom among the Catholic students nowadays. The feeling of the Catholicsm with various of special charachteristics and uniqueness has not enchanted and made the Catholic students proud anymore. They were bored and were uninterested in reek of religion and spiritual as well. The Catholic students should become chief action or chief moving spirit of the pivotal strength of the Church-life in the future, but to be pitfallen slowly or step by step in the crisis of identity of the prolonged Catholicsm. This crisis was caused by their unability to have a certain attitude critically and wisely, accompanied by a gale made the values of secularism that shook various kinds of order belief of the Catholic that has been handed down from one generation to the other. Let the situation has been walking without efforts to overcome it. This condition perhaps would like to destroy the future of the Catholic students. To reply the hindrances needed lots of people to participate actively to give guidance to the them in order to reach the right way. The institute of the highest education as well as the local church are a very important people who must be the right handmen of them. Both of the institutions have to be one mind and sharing in the same struggle to make yourselves appearance or present yourselves as a shepherd to search, to find, and to guide them as the Lambs who have lost their ways to the right ways. The cooperation between two institutions must bear various kinds of contextual activities as well as useful for developing attitude and individuality of them in the future. The activity of spiritual guidance can be done in preparation Parish of St. Marinus Puu’rere is the result of a concern apprehensive together in order to hand them in order that in the middle of a tremendous storm attacking the values of the terrific secularism, the catholic students remained proud of and militant to spout the characteristic of their catholicsm as the light candle for a lot of people through thought, words, and acts which they have done.